Development of a Digital-Based Madiun History Encyclopedia and Its Potential as a History Learning Resource for MAN 4 Madiun - Khoirul Hasanah; Muhammad Hanif; Soebijantoro Soebijantoro (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to develop a digital-based Madiun history encyclopedia and test its feasibility and practicality as a history learning resource for senior high school (SMA/MA) students. The research method employed is Research and Development (R&D), utilizing the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The product is packaged as a ipping book that presents information on Madiun's local history in an interactive and easily accessible manner. Validation by material experts yielded a feasibility level of 82%, while validation by media experts reached 94%. Small-scale practicality trials achieved a percentage of 86%, while large-scale trials reached 87%. Additionally, the percentage from history teachers was 82%. These results indicate that the encyclopedia is a feasible and practical resource for learning history at MAN 4 Madiun.